The impact of private accommodation on economic development of tourist destination-the case of Dubrovnik-Neretva County - Portolan, Ana (Oeconomica Jadertina, 2017)
Private accommodation capacities are a growing segment of the lodging industry in Croatia. In private accommodation capacities 2,684 million tourists were registered in 2010, there were 19,4 million overnight stays, which makes 25% of total arrivals and 34% of total overnights. Although studies have been made on economic impact of tourism on a destination (at the national level), the issues of the impact of private accommodation haven't been given due attention. Consequently, the aim of this paper is to estimate the importance of private accommodation in development of tourist destination on regional level through consumption of tourists accommodated in private capacities, as well as to confirm that tourism receipts realised in private capacities have a positive impact on regional economic development.
Keywords: private accommodation; economic development; tourist destination; Dubrovnik-Neretva County